Functionalized layered double hydroxides for innovative applications. Issue 3 (22nd November 2019) - Laipan, Minwang; Yu, Jingfang; Zhu, Runliang; Zhu, Jianxi; Smith, Andrew T.; He, Hongping; O'Hare, Dermot; Sun, Luyi
Abstract : Functionalization strategies are powerful for generating new or enhanced properties of LDHs, offering unique perspectives and advantages for preparing novel materials. Abstract : Two-dimensional layered double hydroxides (LDHs) are currently a topic of significant interest due to their extraordinary physiochemical properties. LDHs are potentially useful in a wide range of applications, particularly in environmental, energy, catalysis, and biomaterials related fields. Despite the unique intrinsic properties of LDHs, various functionalization strategies have been applied to LDHs that yield even more exciting performance opportunities, offering guides to design novel functional nanomaterials. In this review, we address how these strategies can improve the various properties of LDHs. We provide an overview of the functionalizing strategies of intercalation, surface modification, hybridization, layered compositions regulation, size and morphology control, and defect creation. These strategies contribute significantly to the enhancement of the performance of LDHs, across a diverse range of areas such as adsorptive, catalytic, electronic, electrochemical, and optical. As a result, functionalized LDHs exhibit great potential in a wide range of applications in the environmental and energy domains. We have comprehensively highlighted their emerging potential in the environmental, energy, catalysis, and biomaterials related fields, including heavy metal removal, radionuclide capture, organic contaminants purification, oil pollution elimination, hydrogen generation, supercapacitors, batteries, solar cells, catalysis, and biomaterial fabrication.